Melatonin inhibits chondrosarcoma cell proliferation and metastasis by enhancing miR‐520f‐3p production and suppressing MMP7 expression - Nguyen, Bao Tran; Lin, Chih‐Yang; Chang, Ting‐Kuo; Fong, Yi‐Chin; Thadevoos, Louis Anoop; Lai, Chao‐Yang; Huang, Yuan‐Li; Tsai, Chun‐Hao; Ko, Chih‐Yuan; Liu, Ju‐Fang; Yang, Shun‐Fa; Tang, Chih‐Hsin (Journal of pineal research, 2023)
Chondrosarcoma has a high propensity to metastasize and responds poorly to chemotherapy and radiation treatment. The enzymatic activity of matrix metalloproteinases (MMPs) is very important in chondrosarcoma metastasis. Melatonin exhibits anticarcinogenic activity in many types of cancers by suppressing the expression of certain MMP family members, but this has not yet been clearly determined in chondrosarcoma. Our study demonstrates that MMP7 plays an essential role in chondrosarcoma cell proliferation, migration, and anoikis resistance. We also found that MMP7 is highly expressed in chondrosarcomas. Our in vitro and in vivo investigations show that melatonin strongly inhibits chondrosarcoma cell proliferation, migration, and anoikis resistance by directly suppressing MMP7 expression. Melatonin reduced MMP7 synthesis by promoting levels of miR‐520f‐3p expression, which were downregulated in human chondrosarcoma tissue samples. Pharmacological inhibition of miR‐520f‐3p markedly reversed the effects of melatonin upon chondrosarcoma proliferation and metastasis. Thus, our study suggests that melatonin has therapeutic potential for reducing the tumorigenesis and metastatic potential of chondrosarcoma via the miR‐520f‐3p/MMP7 axis.